LAND USE AND TRANSPORT PLANNING IN THE GREATER KAMPALA, UGANDA - Amin T. Kiggundu; Stephen Mukiibi (Faculty of Geography, Universitas Gadjah Mada, 2012)
Urban land use (also known as spatial planning or urban form) has a big influence andimpact on the way transport systems are planned and managed in large cities. In Kampalafor example, transport systems are largely inefficient because of the failure by the cityauthorities to adopt an integrated approach towards land use and transport planning. Due toa multifarious and complex land tenure system, the provision of roads and other transportrelatedinfrastructure such as parking facilities and bus terminals has become virtuallyimpossible. This paper examines the impact of land use on transport planning in Kampala inview of the city’s recent experience. It also draws lessons from the experiences of the rolemodel cities in Asia. To address key transportation challenges such as rapid motorizationand traffic jam, it is critical that land use-based strategies such as transit malls, land valuecapture, constructing high density buildings (both commercial and residential) along thetransit lines as well as establishing park and ride facilities are adopted by the urbanmanagers and city policy makers.